2013
DOI: 10.4161/epi.27248
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal stability, tissue, and time specific effects ofAHRRmethylation change in response to maternal smoking in pregnancy

Abstract: The intrauterine environment has the potential to "program" the developing fetus in a way that can be potentially deleterious to later health. While in utero environmental/stochastic factors are known to influence DNA methylation profile at birth, it has been difficult to assign specific examples of epigenetic variation to specific environmental exposures. Recently, several studies have linked exposure to smoking with DNA methylation change in the aryl hydrocarbon receptor repressor (AHRR) gene in blood. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
115
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(127 citation statements)
references
References 33 publications
12
115
0
Order By: Relevance
“…Several subsequent studies have now linked exposure to smoking with lower methylation in the AHRR gene (encoding the aryl hydrocarbon receptor repressor). Such changes appear to be stable in the early postnatal period and to be tissue specific [23]. Similar replication of other exposure data is urgently required, as are adequately powered findings that fail to replicate previous associations.…”
Section: Genetic and Environmental Influences On The Early-life Epigementioning
confidence: 85%
“…Several subsequent studies have now linked exposure to smoking with lower methylation in the AHRR gene (encoding the aryl hydrocarbon receptor repressor). Such changes appear to be stable in the early postnatal period and to be tissue specific [23]. Similar replication of other exposure data is urgently required, as are adequately powered findings that fail to replicate previous associations.…”
Section: Genetic and Environmental Influences On The Early-life Epigementioning
confidence: 85%
“…All regions corresponding to the CpG sites significant in this analysis, and all CpG sites themselves, have previously been identified as being associated with smoking [8,12,[33][34][35][36], and discussed with regard to their biological implications in a number of publications, in particular 2q37.1 [8,13,37], AHRR [7,38,39], GFI1 [40], MYO1G [41] and F2RL3 [7,42]. Further, most of these loci have been identified as associated with conditions or diseases also related to smoking.…”
Section: Biological Relevancementioning
confidence: 99%
“…A recent study, using a low-density DNAm array showed detectible prenatal smoking associations in childhood, but could not assess the reported birth sample associations now confirmed by several groups, given the incompatible array content (Breton et al, 2014). A candidate gene-based study (Novakovic et al, 2014) of 11 individuals showed that comparable differences in DNAm at AHRR , a tobacco-related gene, were detectable at birth as well as at 18 months. Finally, a recent longitudinal investigation revealed some smoking-related DNAm alterations, initially detected in their sample at birth, persist within the same individuals over time (Richmond et al, 2014).…”
Section: Introductionmentioning
confidence: 99%